Development and comparison of immunologic assays to detect primary RSV infections in infants - Anderson, Larry J.; Jadhao, Samadhan J.; Hussaini, Laila; Ha, Binh; McCracken, Courtney E.; Gibson, Theda; Yildirim, Inci; Yi, Jumi; Stephens, Kathy; Korski, Chelsea; Kao, Carol; Sun, Heying; et al. (Frontiers in Immunology, 2024)
Effective respiratory syncytial virus (RSV) vaccines have been developed and licensed for elderly adults and pregnant women but not yet for infants and young children. The RSV immune state of the young child, i.e., previously RSV infected or not, is important to the conduct and interpretation of epidemiology studies and vaccine clinical trials. To address the need for sensitive assays to detect immunologic evidence of past infection, we developed, characterized, and evaluated 7 assays including 4 IgG antibody enzyme immunoassays (EIAs), two neutralizing antibody assays, and an IFN-γ EliSpot (EliSpot) assay. The antibody assays were a subgroup A plus subgroup B RSV-infected Hep-2 cell lysate (Lysate) and expressed RSV F protein (F), subgroup A G protein (Ga) and subgroup B G protein (Gb) enzyme immunoassays (EIAs) and a subgroup A and asubgroup B strain neutralizing antibody assays. All seven assays had acceptable repeatability, signal against control antigen, lower limit of detection, and, for the antibody assays, effect of red cell lysis, lipemia and anticoagulation of sample on results. In 44 sera collected from children >6 months after an RSV positive illness, the lysate, F, Ga and Gb IgG EIAs, and the subgroup A and B neutralizing antibody assays, and the EliSpot assays were positive in 100%, 100%, 86%, 95%, 43%, and 57%, respectively. The Lysate and F EIAs were most sensitive for detecting RSV antibody in young children with a documented RSV infection.Unexpectedly, the EliSpot assay was positive in 9/15 (60%) of PBMC specimens from infants not exposed to an RSV season, possibly from maternal microchimerism. The Lysate and F EIAs provide good options to reliably detect RSV antibodies in young children for epidemiologic studies and vaccine trials.